(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to find out the implementation of PKH in the Latellang Village community, Patimpeng District, Bone Regency. This study used qualitative methods and the data sources used observations, interviews, and other data sources as secondary data sources. Data processing and analysis technology had gone through three stages: data reduction, data presentation, and conclusion making. The results of this study were 1) the communication aspect of all administrators in Latellang Village using communication by holding a meeting once a month to maintain communication between the management and beneficiaries, 2) the resource aspect of PKH assistants who did not understand the meaning and adjustment of PKH was so that the delivery of information to participants receiving the assistance had not been maximized, 3) aspects of the bureaucratic structure of procedures or rules that had been in effect with PKH had been followed and obeyed by participants and managers of this program. Keywords: Implementation, PKH, Poverty Alleviation